2017
DOI: 10.3390/ijms18030549
|View full text |Cite
|
Sign up to set email alerts
|

Proline Residues as Switches in Conformational Changes Leading to Amyloid Fibril Formation

Abstract: Here we discuss studies of the structure, folding, oligomerization and amyloid fibril formation of several proline mutants of human stefin B, which is a protein inhibitor of lysosomal cysteine cathepsins and a member of the cystatin family. The structurally important prolines in stefin B are responsible for the slow folding phases and facilitate domain swapping (Pro 74) and loop swapping (Pro 79). Moreover, our findings are compared to β2-microglobulin, a protein involved in dialysis-related amyloidosis. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 94 publications
0
26
1
Order By: Relevance
“…[1][2][3][4][5][6][7] The secondary amino group of Pro creates a tertiary amide-based backbone structure that is prone to cis-trans isomerization issues, which is sometimes responsible for the special role of Pro in protein folding. [4][5][6][7][8] Additionally, the cyclic nature of the Pro residue restricts the molecular conformation to certain envelope-type states of the pyrrolidine ring. [9][10][11][12] As the only coded amino acid with a restricted f torsion, Pro is typically positioned in specific structural contexts in biological systems relative to other amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The secondary amino group of Pro creates a tertiary amide-based backbone structure that is prone to cis-trans isomerization issues, which is sometimes responsible for the special role of Pro in protein folding. [4][5][6][7][8] Additionally, the cyclic nature of the Pro residue restricts the molecular conformation to certain envelope-type states of the pyrrolidine ring. [9][10][11][12] As the only coded amino acid with a restricted f torsion, Pro is typically positioned in specific structural contexts in biological systems relative to other amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…This amino acid can bind to the cations (and thus Se ions) or protons as it contains a single hydrogen atom attached to nitrogen atom (Morgan & Rubenstein, ). Moreover, the hydrophobicity of the proline is considered to play a vital role in disruption of the secondary structure of a protein leading to formation of novel secondary structures (Morgan & Rubenstein, ; Taler‐Vercic et al, ). Moreover, the hydrophobicity of the proline is anticipated to play a vital role in disruption of the secondary structure of a protein leading to formation of novel secondary structures (Morgan & Rubenstein, ; Taler‐Vercic et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the hydrophobicity of the proline is considered to play a vital role in disruption of the secondary structure of a protein leading to formation of novel secondary structures (Morgan & Rubenstein, ; Taler‐Vercic et al, ). Moreover, the hydrophobicity of the proline is anticipated to play a vital role in disruption of the secondary structure of a protein leading to formation of novel secondary structures (Morgan & Rubenstein, ; Taler‐Vercic et al, ). Wu, Ding, Li, Zhang, and Wu () also showed incorporation of selenium into proteins of enriched Lentinus edodes mushroom.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobicity coupled with recognition patterns is suggested to be the key determinants in the interaction between β‐sheet breaker peptides and Aβ peptide . T3 displayed a more pronounced impairment of the aggregation cascade, despite the fact that Pro, a well‐known β‐sheet breaker , is a common residue between T3, T4 and T6. The hydrophobicity indices of all the peptides were calculated , and it was observed that T3 had expressed the highest hydrophobicity of 11.6 (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…The hydrophobicity indices of all the peptides were calculated , and it was observed that T3 had expressed the highest hydrophobicity of 11.6 (Table ). The presence of recurrent Val in T3 possibly provides a better steric zippering as Val and Ile have a strong conformational preference, followed by Pro, which then possibly puts a constraint by inducing a possible cis/trans interconversion resulting in destabilization of the Aβ aggregate .…”
Section: Discussionmentioning
confidence: 99%